Study of elbow carrying angle and its relationship with the length of second and fourth digit - Ravi Kumar Biradar; HM Adarsha (Al Ameen Medical College, 2019)
Background: The acute angle produced medially when the axis of the forearm deviates laterally from the long axis of the humerus, with the arm extended and the palm facing forward, is referred to as the carrying angle. Variations in the angle have clinical as well as pathological significance. Aims and Objectives: This study was conducted to evaluate the elbow carrying angle in normal males and females and its relationship with length of second and fourth digit of same side and also analyse the data to find out any correlation between carrying angle, gender variance due to in utero difference in androgen exposure and ratio of length of ipsilateral second and fourth digit within the study population. Methods: 195 subjects with age varying from 12 to 32 years were studied. Carrying angle was measured using goniometer. Length of second and fourth digit was measured from distal palmar crease to tip of finger. Results: The result of the study showed that carrying angle is more in females than males on both sides. Lower values of carrying angle seen in males is strongly associated with longer ring finger and higher values of carrying angle seen in females associated with a longer index finger. There was only a moderately positive correlation between the carrying angle and fingertip lengths. Conclusion: Carrying angle is greater in women than in men. The second distal fingertip is longer in women and the fourth distal fingertip is longer in men. There is a moderate positive correlation between the carrying angle and the distal extent of fingertip. In utero androgen exposure has an indirect effect on finger length.